The Use of Rice Harvest Residue as Soil Amendment for Growth and Yield of Rice (Oryza sativa L.) on Acid Sulfate Soil - Agus Suyanto; Sri Rahayu; Agnes Tutik Purwani Irianti; Rini Suryani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
The area of rice fields in Indonesia decreased every year. Acid sulfate soil, which was sub-marginal land, had the potential to be converted into rice fields, but it needed improvement, one of which was by using organic materials as ameliorants. This research aimed to obtain the best composition of applying rice harvest residue as an ameliorant on acid sulfate soil in improving the growth and yield of rice. The research was conducted at the greenhouse of Panca Bhakti University Pontianak from January to April 2022. This study used a Completely Randomized Design (CRD). The treatments consisted of: p0: Control, p1: Rice straw = 40 gr/polybag, p2: Rice husk = 40 gr/polybag, p3: Rice husk charcoal = 40 gr/polybag, p4: Rice husk ash = 40 gr/polybag, p5: Rice straw + rice husk, p6: Rice straw + rice husk charcoal, p7: Rice straw + rice husk ash, p8: Rice husk + rice husk charcoal, p9: Rice husk + rice husk ash, p10: Rice husk charcoal + rice husk ash, with each material weighing 20 gr/polybag. The observation variables were plant height, number of tillers, number of productive tillers, dry weight of grains per hill, and 100-grain weight. Analysis of variance used F-test and continued with Least Significant Difference (LSD) test at the 5% level. The application of rice harvest residue had a better effect on the growth and yield of rice than the treatment without the application of rice harvest residue. Treatment p6 had the best effect on the dry weight of grains per hill, which was 65.67 grams. Keywords:   Acidic Sulfate Soils, Ameliorant, Rice, Rice husk charcoal, Straw